Persepsi Mahasiswa Program Studi S1 Pendidikan Tata Rias terhadap Profesi Guru SMK Tata Kecantikan - Fahrani Manikkamila Assyar Halim; Jenny Sista Siregar; Dwi Atmanto (Departement of Mathematics Education, 2024)
This study aims to identify the perceptions of undergraduate students majoring in Beauty Education towards the profession of vocational school (SMK) beauty teachers, examined from the cognitive, affective, and conative aspects of perception. This study employs a descriptive method with a quantitative approach. The sample consists of 55 students selected through purposive sampling. Data were collected using a questionnaire measured on a Likert scale. The results show that the majority of students have a relatively positive perception of the profession of SMK beauty teachers. In the cognitive aspect, students demonstrate a strong understanding of the professional and social competencies of teachers. However, the affective aspect is categorized as low, reflecting less positive attitudes towards teachers' personal competencies and the status and recognition of the profession. The conative aspect shows a moderately positive perception, where students express an interest in pursuing a career as SMK beauty teachers but also consider other career opportunities in the beauty industry. This study suggests increasing awareness regarding the career prospects of SMK beauty teachers to attract more student interest.